Perdagangan Intra Industri Furniture Indonesia Dengan Thailand Sebagai Partner Dagang Tahun 2007-2015 - wishanesta, i kadek donny; Setyari, Ni Putu Wiwin (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
International trade can affect a country's economic growth through exports and imports. One of the forms of cooperation International trade is intra-industry trade cooperation. The relationship between a country with other countries in general to meet the needs among countries. The occurrence of intra trade relations industry to exchange goods or services on two or more state sector in regional economic area agreement. This study aimed to analyze the degree of integration of intra-industry trade furniture Indonesia to Thailand as a trade partner in the year 2007-2015. This study uses Intra-Industry Trade Index (Grubel-Lloyd Index) to calculate the degree of integration. The method of analysis in this study uses an index measuring Intra Industry Trade. The results of this study indicate the degree of integration between Indonesia and Thailand as the country's trading partners in the furniture industry that the level of integration Moderately strong 68.7 until the integration of 95.
Keywords: furniture; Intra Industry Trade Index